KORELASI PENGUASAAN KOSAKATA DENGAN KETERAMPILAN MENULIS TEKS CERITA FANTASI SISWA KELAS VII SMP NEGERI 16 PADANG - Ain, Zamratul; Pramesti, Utami Dewi (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purpose of this research there are three. First, describe vocabulary mastery Class VII students of SMP Negeri Padang 16. Second, it describes the text of the story of fantasy writing skills grade VII JUNIOR Country 16. Third, vocabulary mastery with correlation describes writing skills text story fantasy grade VII SMP Negeri Padang. 16.Â This research type is quantitative descriptive method. The design used in this research is the design korelasional. This research population is grade VII SMP Negeri Padang 16. listed on the 2018/2019 school year, that is 284 students. The sample in this research are determined by proportional random sampling of 20% of the population, i.e. 50 students. Research data is a score test results and score vocabulary mastery test results writing skills text story fantasy. Research instrument is an objective test to measure mastery of vocabulary news and performance tests to measure the writing skills text story fantasy. Based on the results of such research, it can be inferred that the skills of listening text news is correlated with writing skills text news. The better mastery of the vocabulary the better news will also enhance the story text writing skills.Â Kata kunci: Korelasi, Kosakata, Menulis Teks Cerita Fantasi